2021
DOI: 10.1038/s41420-021-00746-z
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-intensity exercise alleviates pyroptosis by promoting autophagy in osteoarthritis via the P2X7/AMPK/mTOR axis

Abstract: Instability and excessive use of the knee joint can cause osteoarthritis (OA). Reasonable exercise can enhance the stability of the knee joint and prevent and relieve the occurrence and development of OA. As a key switch for inflammation, P2X purinoceptor 7 (P2X7) has attracted much attention in studies of OA. Exercise can regulate P2X7 expression and activation. However, the role of P2X7 in exercise-based prevention and treatment of OA is unknown. We previously showed that moderate-intensity exercise can sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 45 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…For instance, the purinergic receptors P2X7 and P2X4, which are primarily activated by extracellular ATP, can initiate NLRP1 and NLRP3-dependent inflammatory responses in OA. 65 , 84 , 85 , 86 AZD9056 is a potent P2X7 receptor antagonist which has shown significant efficacy by downregulating the expression of P2X7, modulating the activation of the NF-κB signaling pathway, and proinflammatory mediators in rats with monoiodoacetic acid-induced (MIA) OA. 87 Another study implemented the same MIA model to test in vivo the P2X7R antagonist, A740003, reporting comparable results.…”
Section: Targeting Inflammasome-dependent Mechanisms In Oamentioning
confidence: 99%
“…For instance, the purinergic receptors P2X7 and P2X4, which are primarily activated by extracellular ATP, can initiate NLRP1 and NLRP3-dependent inflammatory responses in OA. 65 , 84 , 85 , 86 AZD9056 is a potent P2X7 receptor antagonist which has shown significant efficacy by downregulating the expression of P2X7, modulating the activation of the NF-κB signaling pathway, and proinflammatory mediators in rats with monoiodoacetic acid-induced (MIA) OA. 87 Another study implemented the same MIA model to test in vivo the P2X7R antagonist, A740003, reporting comparable results.…”
Section: Targeting Inflammasome-dependent Mechanisms In Oamentioning
confidence: 99%
“…Li et al . found that moderate-intensity exercise promoted autophagy activation through modulating the AMPK/mTOR signaling pathway, resulting in the inhibition of chondrocyte apoptosis and the alleviation of cartilage degeneration in vitro [ 154 ]. Ozone can inhibit the inflammation of OA and regulate cartilage metabolic balance.…”
Section: Reviewmentioning
confidence: 99%
“…However, a recent study demonstrated that moderate-intensity exercise alleviates chondrocyte pyroptosis by promoting autophagy of chondrocyte, which avoids the release of inflammasomes. 104
Figure 3 Mechanical interaction causes osteoarthritis. Abnormal stress and long-term mechanical stimulation upregulate the expression level of chloride channels, which induce the overexpression of osteogenic factors (Runx2, TGF-β, etc).
…”
Section: Mechanical Interaction and Oamentioning
confidence: 99%